ANÁLISE CLÍNICO-EPIDEMIOLÓGICA E SOBREVIDA DE PACIENTES SUBMETIDOS AO TRANSPLANTE DE CORAÇÃO - José Anderson Souza Goldiano (2023)
Heart transplantation constitutes the last therapeutic option for cases of refractory heart failure of functional classes III or IV, and is the gold standard treatment as established by the New York Heart Association, resulting in greater survival and quality of life for the patient. . It is a highly complex procedure, which can generate complex and potentially fatal complications, which can interfere with patient survival, which is currently approximately 70% in five years after transplantation, with a mean overall survival of eleven years. The objective was to analyze the clinical-epidemiological aspects and the survival of heart transplant patients in reference services in Mato Grosso do Sul. This is a study with a quantitative, epidemiological, descriptive, analytical, individual approach, through a single-group retrospective cohort. Data were collected from secondary sources at Hospital Associação Beneficente Santa Casa de Campo Grande and Hospital Caixa de Assistência dos Servidores do Mato Grosso do Sul, referring to the procedures of 22 years of services, from 1999 to 2021. in the second half of 2022. From the study population, all transplant recipients, of both sexes and over 18 years of age, were sampled in a census. Lost medical records were excluded. Data were analyzed using the IBM Statistical Package for the Social Sciences (SPSS®) software, version 24.0, in a descriptive and inferential way. The adopted statistical significance level was 0.05 for all applied tests. Data collection took place after approval of the research protocol by the Research Ethics Committee of the Federal University of Mato Grosso do Sul (Opinion No. 5,303,527) and all the precepts of bioethics were obeyed. The results obtained refer to a final sample of 16 patients, when 68.75% were male; 68.75% hypertensive, 56.25% diabetic, mean age 49.94 years; patients aged over 50 years had a longer survival time, even with successive hospitalizations for cardiac biopsies; average cardiopulmonary bypass time was 137 minutes; 31.25% underwent myocardial revascularization; and regarding the etiology of heart failure, 43.75% were ischemic. It is concluded that despite the sample universe analyzed being small, this study represents all the procedures performed in adult patients over 22 years, therefore, it is important for planning the management and interventions for heart transplant recipients. Knowledge of the variables analyzed and the postoperative period based on the patient's age can provide health professionals with data that enable a more assertive prognostic vision for the prevention of complications and possible graft failures.